2006
DOI: 10.1080/14786410500462702
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid and phenylethanoid derivatives fromKigelia pinnataDC. fruits

Abstract: Further phytochemical investigation of the fruits of Kigelia pinnata DC. has yielded a new phenylpropanoid derivative identified as 6-p-coumaroyl-sucrose (1) together with ten known phenylpropanoid and phenylethanoid derivatives (2-11) and a flavonoid glycoside (12). The structures of the isolated compounds were elucidated using various techniques of NMR and MS spectral analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In a study that qualitatively and quantitatively analyzed the hexane extract for various chemical compositions, it was revealed to contain twelve compounds with the major ones identified as nhentriacontane,1-tricosene, 11-(2, 2-dimethylpropylheneicosane, 2, 6, 10-trimethyldodecane, penta fluoroheptadecyl ester, 2-ethylhexyloctadecyl sulfurous acid ester, heneicosane and hexyloctylsulfurous acid ester [55,56,57] Others are 4, 4-dimethylundecane, methyl-12-methyltetradecanoate, 1-iodohexadecane and 1-iododecane.Hentriacontane have been reported to have a possible antitumor activity while methyl-12-methyltetradecanoate has also been reported for its inhibition capacity on the development of coneal angiogenesis, which is responsible for blindness and other infections [44] Flavonoids and iridoids [45] and a 7-O-glucoside have also been found in the leaves ( Table 2). The structural formulae of some of the chemical constituents isolated…”
Section: Chemical Constituents Of Kigelia Africana Leafmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that qualitatively and quantitatively analyzed the hexane extract for various chemical compositions, it was revealed to contain twelve compounds with the major ones identified as nhentriacontane,1-tricosene, 11-(2, 2-dimethylpropylheneicosane, 2, 6, 10-trimethyldodecane, penta fluoroheptadecyl ester, 2-ethylhexyloctadecyl sulfurous acid ester, heneicosane and hexyloctylsulfurous acid ester [55,56,57] Others are 4, 4-dimethylundecane, methyl-12-methyltetradecanoate, 1-iodohexadecane and 1-iododecane.Hentriacontane have been reported to have a possible antitumor activity while methyl-12-methyltetradecanoate has also been reported for its inhibition capacity on the development of coneal angiogenesis, which is responsible for blindness and other infections [44] Flavonoids and iridoids [45] and a 7-O-glucoside have also been found in the leaves ( Table 2). The structural formulae of some of the chemical constituents isolated…”
Section: Chemical Constituents Of Kigelia Africana Leafmentioning
confidence: 99%
“…Gouda and colleagues [45] reported that a new furanone derivative formulated as 3-(2'-hydroxyethyl) -5 -(2'' hydroxypropyl) dihydrofuran -2 -(3H)one and four new iridoids named: 7-hydroxyviteoid II, 7-hydroxyeucommic acid, 7 -hydroxy-10-deoxyeucommiol and 10-deoxyeucommiol have been isolated from the fruits in addition to seven known iridoids namely, jiofuran, jioglutolide, 1-dehydroxy -3, 4 -dihydroaucubigenin, des -p -hydroxy benzoyl kisasagenol B, ajugol, verminoside and 6-transcaffeoyl ajugol. Further phytochemical investigation of the fruits of Kigelia Africana yielded a new phenylpropanoid derivative identified as 6-p-coumaroylsucrose together with ten known phenylpropanoid and phenylethanoid derivatives and a flavonoid glycoside.…”
Section: Chemical Constituents Of Kigelia Africana Fruitmentioning
confidence: 99%
“…Various chemical investigations have been carried out on K. africana and many chemical compounds mainly iridoids, naphthaquinones, monoterpenoidnapht-haquinones, isocoumarins, caffeic acid, norviburtinal, lignans, sterols and flavonoids have been identified (Gabriel and Olubunmi, 2009). Chemical analysis of the polar extract of fruit indicated the presence of vermonosides (Picerno et al, 2005), phenylpropanoid derivative identified as 6-p-coumaroyl-sucrose, and flavonoid glycoside (Gouda et al ., 2006). Herein, we report the green synthesis and antimicrobial studies of silver nanoparticles (AgNPs) along with the bimetallic copper-silver nanoparticles mediated by aqueous extract of K. africana fruits.…”
Section: Introductionmentioning
confidence: 99%
“…[5,20] Several compounds have also been isolated and identified from fruit extracts, including vermonoside, 6-p-coumaroyl-sucrose, sitosterol-7-O-glucoside, 19a-dihydroxyurs-12-ene-28oic acid, coumaric acid (Figure 1h), caffeic acid (Figure 1i), ethylgallic acid (Figure 1j) and chlorgenic acid. [10,[21][22][23] Of these, vermonoside may be of particular interest as an anti-protozoal compound due to its reported antiamoebic activity. [24] The current study was undertaken to extend the previous antibacterial and antifungal studies of K. africana fruit against a more extensive microbial panel.…”
Section: Introductionmentioning
confidence: 99%